Efektivitas Dukungan Ventilasi terhadap Pola Napas pada Pasien Tuberkulosis di IGD RS TK. II Pelamonia Makassar - Nur Haeni; Sudarman Sudarman; Wan Sulastri Emin; Akbar Asfar (Rumah Sakit Ibnu Sina, Makassar, 2025)
Pulmonary tuberculosis may impair ventilation and increase the work of breathing, placing patients at risk of an ineffective breathing pattern. This case report describes nursing support for ventilation through nurse-led interventions of pursed-lips breathing (PLB) and the semi-Fowler position in a pulmonary tuberculosis patient with an ineffective breathing pattern diagnosis. A descriptive single case report was prepared following CARE guidelines and the nursing process. Observation was conducted for 24 hours in a 69-year-old male patient in the emergency department of RS TK II Pelamonia Makassar. Outcomes were recorded consistently at baseline (March 17, 2025, 10.00 WITA) and at 24-hour follow-up, including respiratory rate (RR), oxygen saturation (SpO₂), signs of respiratory distress, and dyspnea using the Modified Borg Dyspnea Scale. Nurse-led interventions (semi-Fowler 30–45° and structured PLB) were implemented alongside collaborative therapy (oxygen via nasal cannula at 4 L/min and nebulized combivent/pulmicort) as prescribed. Clinical improvement was observed in this case, indicated by a decrease in RR from 25 to 22 breaths/min, an increase in SpO₂ from 96% to 100%, and a decrease in Borg score from 5/10 to 3/10, accompanied by reduced accessory muscle use. Conclusion: the nursing care package (PLB and semi-Fowler position) together with collaborative therapy was followed by improved breathing outcomes in a single pulmonary TB case; causality and generalization are limited and further studies are needed.